(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
The study of hose whip phenomenon is a significant part for further researching dynamic characteristics of hose-drogue system during the aerial refueling operation. The hose whip phenomenon in hose-drogue aerial refueling is simulated based on a high-efficiency neighbor-to-neighbor algorithm. The Osher scheme and SA turbulence model are employed to solve the compressible Navier-Stokes equations, and the hose is discretized into a series of ball hinges linked by massless rigid links which form a multi-body system, the kinematical and dynamic equations are then derived for the system. The numerical model is used to simulate the hose-drogue system dynamics in multiple conditions. The results show a good correlation with previously reported flight-test data in open literature and the application of neighbor-to-neighbor algorithm saves a lot of computational cost. Results of this study may have certain guiding significance for the probe-and-drogue aerial refueling.